On the impact of motion-thrust coupling in floating tidal energy applications. (15th January 2021) - Brown, S.A.; Ransley, E.J.; Xie, N.; Monk, K.; De Angelis, G.M.; Nicholls-Lee, R.; Guerrini, E.; Greaves, D.M.
Abstract: Floating systems provide an opportunity to expand the available tidal stream energy resource and reduce the levelised cost of energy by increasing the number of viable deployment sites; simplifying the installation, maintenance and decommissioning; and by accessing greater flow speeds near the free surface. However, the inevitable exposure to free surface conditions raises questions over both the power delivery and the survivability of these systems, both due to the presence of waves and the associated excitation of the floating structures. Without addressing these concerns through scale modelling in laboratories and prototype deployments, the risk to investors is too high to gain significant support for the industry. Therefore, this paper presents physical modelling and analysis of a 1:12 scale model of the Modular Tide Generators floating tidal platform concept, a pseudo-generic design consisting of a catamaran-style platform, catenary mooring system and a submerged horizontal axis tidal turbine. The behaviour of the full system is explored in a range of wave, current, and following wave–current conditions; with and without the turbine; and in rigidly fixed and moored configurations. The results imply that a linear superposition of waves and currents is an adequate modelling approach for determining the mean and cyclic values for the mooring loads and motion of the system. However, the loading on, and power generated by, the turbine are more complex and have implications for power delivery quality and the lifespan of the turbine. In particular, the magnitude of the cyclic loading increases with the current speed, as well as the surge and pitch motion which is observed to be most influential near harmonics of the pitch resonance frequency. Highlights: Incremental laboratory tests of a proposed floating tidal concept are presented. Mean surge equilibrium is altered by the turbine but cyclic motion is insensitive. Cyclic turbine load increases with current speed due to wave–current interactions. Platform motion amplifies the cyclic turbine load especially at peak pitch harmonics. Motion-thrust coupling is sensitive to the relative phases of motion and wave.